Dog bite injuries in children: Clinical implications for head involvement. (July 2016) - Sribnick, Eric A; Sarda, Samir; Sawvel, Michael S; Reisner, Andrew; Chern, Joshua J
Background: Given the popularity of dogs in the United States, children with dog bite injuries represent a significant health concern. While dog bite injury in any area of the body can lead to significant morbidity and potential mortality, dog bite injury to the head tends to occur in younger children and leads to more significant pathology. Methods: This study presents data obtained from retrospective analysis of a trauma database from a single, urban pediatric hospital system. Data were gathered over more than eight years and includes 236 patients. We examined patient demographics, dog breed involved, hospital course and treatment, infection rate, antibiotic use, and disposition. Results: Of the 236 total patients, 174 patients had head involvement with the injury. The dog involved tended to be an animal owned by a family member or family friend. Patients who had head involvement tended to be younger than those without head involvement. Head injury correlated with a significant increase in the number of surgeries required. The two deaths were exclusively in children under three months of age who had head involvement. Patients given antibiotic prophylaxis with amoxicillin/clavulanic acid were associated with a lower rate of post-injury infection than patients on other forms of antibiotic prophylaxis, and patients treated without antibiotic prophylaxis had a lower infection than those treated with prophylactic antibiotics. Conclusions: Dog bites in children represent a significant, preventable cause of morbidity and mortality. Our data suggest that young children are especially vulnerable and dog–child interactions should be monitored closely, even when the dog is familiar to the child.